OPTIMIZATION OF THE METHODS CHOICE OF PLASTICS VENTRAL HERNIA REPAIR IN PATIENTS WITH OBESITY - Лавренко, Д.О. (World of Medicine and Biology, 2015)
In the context of the surgical department of a multi-hospital between 2010 and 2015, 146 patients were treated with ventral grizhami and obesity. Of these, 24 (16.4%) men and 122 (83.5%) women. Patients ranged in age from 25 to 82 years. The average age of patients was 53 years. Selection of surgical treatment was planned based on the results of preoperative examinations. In the process of multi-factor studies have established criteria for selecting hernia repair, among which are the dominant component of intra-abdominal pressure and the size of the hernia defect. Thus autoplasty methodology should be applied in plastic small hernias. When the allogernioplastiki advantage should be given to the method of "sublay", the method "іnlay" - forced to use a deficiency of tissue at the site of the hernia defect.
Keywords: ventral hernia; obesity; abdominal pressure